ASSESSING THE IMPACT OF CONVERGENT THINKING ABILITY ON ENGLISH SPEAKING PROFICIENCY - Humaira, Tasnova (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
Speaking in English is an important skill to master to gain an upper hand in a person’s academic and professional life. Different countries, where English is considered to be a foreign language, are emphasizing developing English language learning and teaching strategies to gain the status of globalization. To achieve this goal, English speaking skills play a crucial role as it is an effective mode of communication to connect with the world. This created an immense need to research how to develop the speaking skills of students studying at the university level. Therefore, this study researched the impact of convergent thinking ability to enhance English speaking proficiency among students. The instrument used to obtain the results are—Remote Associates Test (RAT) and Speaking Proficiency English Assessment Kit (SPEAK). At the end of the research, it was determined that if the education sector focuses on developing students' convergent thinking ability then the process of enhancing English speaking proficiency becomes easier.